Real-time pcr-based detection and quantification of porcine adulteration in processed gelatin and gelatin capsule - Mohamad, Nurhidayatul Asma (2017)
Species adulteration using DNA-based method in highly processed products such as gelatin and gelatin capsule has not been widely studied. Execution of the method has been challenged by the minute amount of DNA trapped in the complex structure of the gelatin matrix which is difficult to be extracted. Furthermore, the DNA is highly degraded due to exposure to extreme processing conditions. Thus, an efficient DNA extraction method and sensitive detection analysis are required. In this study, a DNA extraction method from gelatin was optimized by increasing the sample incubation period for lysis, incorporating additional sample homogenization step and adjusting the pH of the solution prior to DNA precipitation. Then, DNA fragmentation was analysed by amplifying approximately 100 bp to 300 bp target sequence in the sample. For detection and quantification analysis, highly specific and sensitive molecular beacon real-time PCR assays were designed to detect porcine in gelatin and gelatin capsule samples. As a control, endogenous PCR assay was derived from mitochondrial-encoded 16s rRNA gene (16S). On the other hand, porcine-specific assays were designed using cytochrome b gene (CBH) and animal repetitive element MPRE42 (MPRE) where their performance were characterized in terms of sensitivity, limit of detection (LOD), linearity and efficiency. To determine porcine content in gelatin and gelatin capsule samples, the calibration curve for each PCR assay was constructed using cloned plasmid DNA standards containing the target sequence of each of the PCR assay and validated using an external standard which is laboratory-prepared 50% (w/w) of meat admixtures. Good quality DNA was successfully extracted from gelatin samples where the interaction of the DNA and gelatin was disrupted by adjusting the pH of the solution to higher pH upon DNA precipitation. Whilst, no positive effect has been observed from additional homogenization and prolong sample incubation. Besides, gelatin DNA has been found to contain as large as 300 bp DNA fragment. The molecular beacon real-time PCR assays developed were highly sensitive where they can detect down to 0.1 pg pork DNA. MPRE PCR assay exhibited higher sensitivity for gelatin DNA as compared to CBH PCR assay as it can detect down to 1 pg DNA compared to 10 pg DNA. This depicts better performance of chromosomal DNA-based PCR assay in porcine detection. In contrast, mitochondrial-encoded CBH PCR assay gave better estimation in quantification of porcine content as compared to MPRE PCR assay depicted by lower error of 8% as compared to 23% obtained upon validation using 50% (w/w) of meat admixture. DNA-based porcine detection method has been successfully established in this study involving the efficient DNA extraction method, highly specific and sensitive porcine detection analysis and efficient DNA quantification method. These methods can be applied for halal authentication as well as to solve halal issues regarding gelatin and gelatin capsule products available in the market.